Once a teacher always a teacher: The stories of two art educators who left public schools. (April 2022) - Bain, Christina; Young, Jeff; Kuster, Deborah
Abstract: The purpose of this instrumental case study was to investigate why two K-12 art educators, participants of a longitudinal study, left public school employment. Data was collected through semi-structured interviews and inductively analyzed. Due to the small sample size, results are not generalizable, but their stories provide an alternative narrative focusing on teaching as a career. Our participants were generally satisfied in their jobs, continue to apply many of their teaching skills in their new positions, continue to view themselves as educators, and are open to returning to public school classrooms at some future point. Highlights: Dissatisfaction with public school employment not main reason our participants left K-12 employment. Participants still identify as teachers, using pedagogical skills and knowledge in new settings. Job fluidity – Teaching can be conceptualized as career with multiple phases/locations. Despite job satisfaction, changing dynamics in personal lives influenced employment changes.